2017
DOI: 10.2147/jpr.s131434
|View full text |Cite
|
Sign up to set email alerts
|

Bottlenecks in the development of topical analgesics: molecule, formulation, dose-finding, and phase III design

Abstract: Topical analgesics can be defined as topical formulations containing analgesics or co-analgesics. Since 2000, interest in such formulations has been on the rise. There are, however, four critical issues in the research and development phases of topical analgesics: 1) The selection of the active pharmaceutical ingredient. Analgesics and co-analgesics differ greatly in their mechanism of action, and it is required to find the most optimal fit between such mechanisms of action and the pathogenesis of the targeted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…118 Centrally, amitriptyline behaves largely as a serotonin-norepinephrine reuptake inhibitor; however, the topical effects of amitriptyline are believed to include antagonism of voltage-gated ion channels and a number of other receptors (eg, adrenergic, cholinergic, histaminergic, muscarinic, and N-methyl-D-aspartate receptors). 119 Applying cool temperatures to the skin can reduce itch intensity and duration. 120 This mechanism involves activation of TRPM8 on afferent neurons, which can then activate inhibitory pathways to reduce itch (Fig 2).…”
Section: Anesthetics and Drugs Targeting Transient Receptor Potentialmentioning
confidence: 99%
“…118 Centrally, amitriptyline behaves largely as a serotonin-norepinephrine reuptake inhibitor; however, the topical effects of amitriptyline are believed to include antagonism of voltage-gated ion channels and a number of other receptors (eg, adrenergic, cholinergic, histaminergic, muscarinic, and N-methyl-D-aspartate receptors). 119 Applying cool temperatures to the skin can reduce itch intensity and duration. 120 This mechanism involves activation of TRPM8 on afferent neurons, which can then activate inhibitory pathways to reduce itch (Fig 2).…”
Section: Anesthetics and Drugs Targeting Transient Receptor Potentialmentioning
confidence: 99%
“…94 TA B L E 3 Prospective trials of ketamine for procedural pain or sedation in children with cancer (sample size ≥ 10) and decreased risk of abuse or dependence. 95 Considering these benefits and the fact that the patients with cancer are already on a concoction of systemic agents, discovering effective topical agents could prove very useful in this group in providing desired therapeutic effects while minimizing adverse effects and harmful drug interactions. 96 Hence, further studies investigating the topical delivery of ketamine for analgesic and anti-inflammatory effects need to be encouraged.…”
Section: Topical Ketaminementioning
confidence: 99%
“…Without wanting to go too much into detail here, various physicochemical characteristics, such as molecular weight, melting point, the partition coefficient, the capacity factor, and aqueous saturation solubility, all play important roles [12]. For instance, in order to penetrate the outer skin layer, a compound needs to have lipophilic characteristics and a relatively low molecular weight; it needs to be a small molecule [8]. Furthermore, the compounds need to be soluble in the selected vehicle, which in turn needs to be smearable, non-sticky and not unpleasant for patients when they rub it in.…”
Section: Selecting (Co-)analgesics For Topical Formulationsmentioning
confidence: 99%
“…Studies comparing the combination of amitriptyline 2% and ketamine 1% to placebo were found to be negative [6,7]. We felt that dose-ranging in topical studies has been conducted in a suboptimal way, and one should aim for much higher dose-ranges [8].…”
Section: Introductionmentioning
confidence: 99%